Cheese as Functional Food: The Example of Parmigiano Reggiano and Grana Padano - Summer, Andrea; Formaggioni, Paolo; Franceschi, Piero; Di Frangia, Federica; Righi, Federico; Malacarne, Massimo (Food technology and biotechnology, 2017)
Italian hard cooked types of cheese, like Parmigiano Reggiano and Grana Padano, are characterised by positive nutritional qualities. In fact, they contain substances that have particular biological activities, and therefore they can be fully considered, according to the definition given by the European Unit, as 'functional' foods. This short review concisely describes these components and the beneficial effects related to their activities. The description of the biologically active components has been organised in the following paragraphs: protein and peptides, fat and lipids, carbohydrates and prebiotics, probiotic bacteria, vitamins, mineral salts, and components of dairy products active in disease prevention. In particular, several known bioactive peptides were found in Parmigiano Reggiano cheese samples: for example, phosphopeptides, which are known for their mineral-binding capacity and vehiculation activity, peptides with immunomodulatory activity, and angiotensin-converting enzyme-inhibitory peptides with anti-hypertensive effects. Among lipids, the role of conjugated linoleic acid and other fatty acids present in these cheese types was taken into consideration. The presence of oligosaccharides with prebiotic properties and probiotic bacteria was also described. Finally, particular emphasis was given to highly available calcium and its impact on bone health.